2021
DOI: 10.1111/crj.13336
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and BMI with FEV1 in non‐hypoxemic COPD out‐patients

Abstract: Objectives This study was conducted to determine the impact of insulin resistance using Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR) score and BMI in non‐hypoxemic out‐patients with COPD on FEV1 using linear and polynomial regressions and to determine their correlation. Methods COPD patients of both genders were included after informed consent. Fasting blood sugar and serum insulin were done to calculate HOMA‐IR, which were segregated into two groups of ≥ 3 and < 3 labeled insulin resistance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…42 A previous study has shown that hyperinsulinaemia has a negative impact on lung function. 43 COPD patients have a higher prevalence of insulin resistance, [44][45][46] which is associated with skeletal muscle weakness in COPD. 47 In addition, a retrospective study reported that BMI was moderately correlated positively with pulmonary function and negatively with exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…42 A previous study has shown that hyperinsulinaemia has a negative impact on lung function. 43 COPD patients have a higher prevalence of insulin resistance, [44][45][46] which is associated with skeletal muscle weakness in COPD. 47 In addition, a retrospective study reported that BMI was moderately correlated positively with pulmonary function and negatively with exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with the results of previously published studies using HOMA-IR to assess insulin resistance. 10 , 11 , 15 , 26 , 27 Zuberi et al assessed HOMA-IR index in relation to COPD and found a high prevalence of insulin resistance in non-hypoxaemic COPD. 26 The relationship between insulin resistance using HOMA-IR index and lung function has been found in relation to lung volumes and it has therefore been suggested that this relationship may reflect childhood exposures that affect both lung growth and programming effects on insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 15 , 26 , 27 Zuberi et al assessed HOMA-IR index in relation to COPD and found a high prevalence of insulin resistance in non-hypoxaemic COPD. 26 The relationship between insulin resistance using HOMA-IR index and lung function has been found in relation to lung volumes and it has therefore been suggested that this relationship may reflect childhood exposures that affect both lung growth and programming effects on insulin sensitivity. 15 The effects of insulin and insulin resistance on the lung and airways have been found to begin early in life.…”
Section: Discussionmentioning
confidence: 99%
“…However, obesity can contribute to the development of insulin resistance and DM, both prevalent comorbidities in COPD patients [13]. The presence of DM and certain nutritional alterations can cause a deterioration in overall health status and quality of life in patients during both periods of stability and severe exacerbations [14].…”
Section: Introductionmentioning
confidence: 99%